Pressure and Permeability Evolution near Hydrate Exploitation Well During Constant-Rate Water Flooding: An Experimental Study - Yuning Liu; Yunkai Ji; Qiang Fu; Zhenyu Zhu; Zihao Wang; Gaowei Hu; Qiang Chen; Yongchao Zhang; Qingtao Bu; Yizhao Wan (Journal of Marine Science and Engineering, 2026)
Dynamic damage to the seepage characteristics of the near-well zone during natural gas hydrate exploitation is a key factor limiting production stability. There is still a lack of systematic understanding of the microscopic mechanisms underlying fine-particle migration and blockage in the near-well zone. In this study, a long sand-packed column was segmentally packed with clayey-silt sediments from the South China Sea and quartz sand to simulate the near-well reservoir and the packed layer, respectively. Long-term seepage processes in the near-well zone were simulated using water flow experiments at constant flow velocities. By combining pressure distribution monitoring with particle-size analysis, the spatiotemporal evolution of seepage characteristics in the near-well zone is revealed from both macroscopic and microscopic perspectives. Results indicate that under long-term displacement, the reservoir permeability near the injection end increased from 0.0149 mD to 0.0159 mD; the reservoir permeability near the packed layer exhibits the greatest decline, dropping from 0.0089 mD to 0.0065 mD. Combined with the particle-size analysis of the packer layer, the boundary between the reservoir and the packed layer is identified as the critical site for permeability damage in the near-well zone. Radial flow inversion shows that a reduction in wellbore radius leads to an increase in reservoir pressure, with the increase being greater the farther from wellbore. A decrease in the permeability of packed layer causes an increase in reservoir pressure, but the magnitude of the increase is consistent across different locations. It provides a theoretical basis for the optimized design of production wells.

Integrated hydrogen system analysis across the resource-environment-economy nexus: a case study of China - Maximilian Arras; Anne Yingqiu Liang; Yuning Fu; Zheng Li; Linwei Ma (Journal of Industrial Ecology, 2026)

Insight into homogeneous activation of sodium hypochlorite by dithionite coupled with dissolved oxygen (DO@NaClO/DTN) for carbamazepine degradation - Wei Song; Hongze Fang; Zhaosheng Lei; Ruigang Wang; Caixia Fu; Fei Wang; Yuning Fang; Xing Du; Zhihong Wang; Zhiwei Zhao (Water Research, 2025)

Dissolved oxygen activated by single-atom-state iron coupled with sodium dithionite for norfloxacin degradation: Efficiency and mechanism - Wei Song; Sen Xu; Caixia Fu; Ruiyi Huang; Hongze Fang; Li Li; Dachao Lin; Yuning Fang; Xing Du; Zhihong Wang (Journal of Cleaner Production, 2025)

Synergistically enhanced heterogeneous activation of dissolved oxygen for aqueous carbamazepine degradation over S(III) coupled with siderite - Yuning Fang; Fei Wang; Hongze Fang; Zhaosheng Lei; Wei Song; Caixia Fu; Xing Du; Zhihong Wang; Zhiwei Zhao (Environmental Pollution, 2024)

Transforming waste polystyrene foam to carbon on zeolite for efficient solar water desalination - Mingxin Yang; Hao Zhang; Yuning Fu; Zixuan Wang; Ying Zhang; Zhongwang Ding; Mingbo Yue (Journal of Environmental Chemical Engineering, 2024)

Degradation of sulfamethazine in coastal aquaculture tailwater by Na2S2O4@iron-electrode electrooxidation combined with ceramic membrane process - Wei Song; Yuning Fang; Hongze Fang; Deming Gu; Xing Du; Sen Xu; Caixia Fu; Yu Zhou; Zhihong Wang (Environmental Pollution, 2024)

In situ conversion of ZnO anchored on porous carbon foams to antiflexible ZIF-8-X (X = Co or NH2) for sieving linear and mono-branched hexane isomers - Xufei Li; Yankang Zhou; Weiqiu Huang; Xinya Wang; Yuning Li; Lipei Fu; Jing Zhong; Lin Liu (Chemical Engineering Journal, 2024)

Single and combined toxicity assessment of primary or UV-aged microplastics and adsorbed organic pollutants on microalga Chlorella pyrenoidosa - Wei Song; Caixia Fu; Yuning Fang; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Kalpana Bhatt; Lu Liu; Ningjie Wang; Fang Liu; Shunni Zhu (Environmental Pollution, 2023)

Seasonal hydrological loading from GPS observed data across contiguous USA using integrated R and Hadoop-GIS framework - Pece V. Gorsevski; Yuning Fu; Kurt S. Panter; Asanga M. Ramanayake; Jeffrey Snyder (Arabian Journal of Geosciences, 2021)

Linking Oceanic Tsunamis and Geodetic Gravity Changes of Large Earthquakes - Yuning Fu; Y. Tony Song; Richard S. Gross (Pure and Applied Geophysics, 2017)

The effect of using inconsistent ocean tidal loading models on GPS coordinate solutions - Yuning Fu; Jeffrey T. Freymueller; Tonie van Dam (Journal of Geodesy, 2012)

Analysis of gene expression profile in pollen development of recessive genic male sterile Brassica napus L. line S45A - Yuning Chen; Shaolin Lei; Zhengfu Zhou; Fangqin Zeng; Bin Yi; Jing Wen; Jinxiong Shen; Chaozhi Ma; Jinxing Tu; Tingdong Fu (Plant Cell Reports, 2009)

Fine mapping of the recessive genic male-sterile gene (Bnms1) in Brassica napus L. - Bin Yi; Yuning Chen; Shaolin Lei; Jinxing Tu; Tingdong Fu (Theoretical and Applied Genetics, 2006)